Upper limb phlegmasia cerulea dolens treated with single-session suction thrombectomy: a case report - Ghaly, Paul (J Surg Case Rep, 2020)
Phlegmasia cerulea dolens (PCD) of the lower limbs is a rare condition. PCD of the upper limbs is extremely uncommon, with only a select few cases documented in the literature. A complication of severe deep venous thrombosis, PCD, is characterized by the clinical triad of oedema, pain and limb cyanosis. Delays in treatment are associated with high rates of morbidity and mortality. We present a case of sudden-onset upper limb PCD in a 68-year-old man following haemodialysis through a long-term arteriovenous fistula. Prompt diagnosis and rapid initiation of intravenous anticoagulation followed by urgent single-session suction thrombectomy resulted in the successful restoration of vessel patency without any significant adverse sequelae on 3-month follow-up.